The tensile strength of layered bovine amniotic membrane and human amniotic membrane for periodontal guided tissue regeneration: Kekuatan tarik layered bovine amniotic membrane dan human amniotic membrane untuk periodontal guided tissue regeneration - I Komang Evan Wijaksana; Made Talitha Suryaningsih Pinatih (Makassar Dental Journal, 2024)
This article aims to compare the tensile strength of coated bovine amniotic membrane (BAM) and human amniotic membrane (HAM) to assess the suitability of BAM as an alternative to HAM for periodontal guided tissue regeneration (GTR). Freeze-dried BAM (FDBAM) and freeze-dried HAM (FDHAM) were used as samples. The tensile strength of FDBAM and FDHAM was tested with an elongation rate of 10 mm/min. Five samples of each type of material coated with 2, 4, 6, 8, and 10 layers were tested. Data were statistically analysed (α=0.05). Tensile strength tests showed that FDBAM had consistently higher tensile strength (p<0.05) compared to FDHAM in all layers measured. The increase in tensile strength of the amniotic membrane was not proportional to the increase in number of layers for both FDBAM and FDHAM. The highest tensile strength of FDBAM was found in the 6-layer sample, and the lowest in the 10-layer. The highest tensile strength of FDHAM was found in the 4-layer, and the lowest in the 2-layer sample. It is concluded that FDBAM has a higher tensile strength compared to FDHAM. The tensile strengths of FDBAM and FDHAM fulfil the minimum criteria for GTR membranes. FDBAM can be considered as a replacement for FDHAM as a mem-brane in periodontal GTRs because tensile strength is a very important factor.